Requisitos para contratação de profissionais de apoio escolar nos sistemas estaduais de educação - Piovezan, Camila Carlini Bonilha (Universidade Federal de São Carlos, 2022)
In the schooling scenario of students Target Public of Special Education (PAEE) there are several actors: special education teacher, regular classroom teacher, management team, health professionals and also professionals who support the student PAEE. One of these is described in the Brazilian Inclusion Law - LBI as a school support professional (PAE), whose responsibilities involve the student's food, hygiene and locomotion activities. The legislation provides for the entry of this professional in the school and the demand for it has been growing, particularly after the growth of enrollments of PAEE students in common schools and the approval of LBI. This law guaranteed a legal provision for this type of support and defined the role of these professionals, favoring their hiring, since the education systems are regulating this profession in guiding documents based on the law. In view of this, the following guiding question arises: Through the legal provision (LBI), of the profession of the support professional being recent, how are the systems regulating the hiring of PAEs? The general objective of the study was based on describing and analyzing how the education networks are regulating the hiring of school support professionals, considering the regulated attributions, positions, functions and working conditions. This research took place through the method of document analysis. Data collection was carried out in two stages: the first stage was the search for the websites of the Departments of Education and/or Special Education to investigate whether they mentioned support professionals. The document survey stage aimed to verify the available material on the subject. The next step of the research was to find the State Education Plans (PEE) of the states and the Federal District (PDE) and to see if they mentioned support professionals. Data analysis took place in two stages: the first, the selection and organization of the material and, in the second, the categorization of the data that were divided into two axes: PEE (Term, State and Nomenclature used) and Selective Processes (Forms of hiring, Nomenclature, Contractual regime, Required Training, Salary and other benefits, working hours and assigned functions - Assignments for the position and Requirements). The initial hypothesis was that there would be few laws covering support professionals, as well as their attributions, forms of hiring and level of education, which could give them incipient visibility. However, the results indicate that the laws are not uniform, as they name these professionals in different ways, even though their attributions are similar. They showed the urgency of discussion regarding the selection criteria of these professionals in consensus with the studies highlighted in the research. The selection of PAEs must be thought of urgently and carefully, resulting in other factors, a better performance and quality of the services provided. The present study met the proposed objectives regarding the understanding of working conditions, hiring regimes and the functions assigned to these professionals, assuming, therefore, the role of triggering new investigations on the subject. It is concluded that the inexistence of a specific law that contemplates the PAEs has culminated in deregulation, and there may be cheapening and precariousness of its workforce. For further studies, it is proposed to deepen public policies, involving support networks and emphasizing the role of PAEs in the context of Special Education
Requirments for the hiring of school support oficials in the state education systems
Keywords: Educação Especial; inclusão Escolar; Estados brasileiros; Profissional de apoio; Special Education; School inclusion; Brazilian states; Support professional; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO